Application of preoperative endoscopic ultrasonography-guided carbon nanoparticle tattooing combined with titanium clip labeling in esophagogastric junction adenocarcinoma - Lin, Lan; Wang, Ming; Hong, Jie; Yang, Sheng; Wang, Yu (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Lin L, Wang M, Hong J, Yang S, Wang Y. Application of preoperative endoscopic ultrasonography-guided carbon nanoparticle tattooing combined with titanium clip labeling in esophagogastric junction adenocarcinoma. Turk J Gastroenterol 2019; 30(10): 935-6.